2008
DOI: 10.1016/j.electacta.2008.04.081
|View full text |Cite
|
Sign up to set email alerts
|

Spectroelectrochemical analysis of ion-transfer and adsorption of the PAMAM dendrimer at a polarized liquid|liquid interface

Abstract: Interfacial behavior of the fourth generation polyamidoamine (G4 PAMAM) dendrimer at the water|1,2-dichloroethane (DCE) interface was studied by the cyclic voltammetry and the potential modulated fluorescence (PMF) spectroscopy.The irregular voltammetric responses were observed at positively polarized interfaces. Cyclic voltammogram was strongly dependent on pH and concentrations of G4 PAMAM dendrimer and organic supporting electrolyte. PMF spectroscopy was successfully used for analyzing the interfacial mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…As reported previously, the positive peak observed around 0.40 V assigned as ion transfer of the G4 PAMAM dendrimer from the aqueous to the organic phases, and negative peak around 0.30 V as the back transfer from the organic to the aqueous phases. 16,32 In addition, a gradual increase of current response at the positive edge of the potential window Figure S8). The absence of apparent transfer responses in the corresponding potential region would demonstrate that the porphyrin molecules are stably associated with the dendrimers even at the polarized water|DCE interface.…”
Section: Ion Transfer Behavior Of Dendrimer-porphyrin Associates At Tmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported previously, the positive peak observed around 0.40 V assigned as ion transfer of the G4 PAMAM dendrimer from the aqueous to the organic phases, and negative peak around 0.30 V as the back transfer from the organic to the aqueous phases. 16,32 In addition, a gradual increase of current response at the positive edge of the potential window Figure S8). The absence of apparent transfer responses in the corresponding potential region would demonstrate that the porphyrin molecules are stably associated with the dendrimers even at the polarized water|DCE interface.…”
Section: Ion Transfer Behavior Of Dendrimer-porphyrin Associates At Tmentioning
confidence: 99%
“…The spectroelectrochemical analysis demonstrated that the amino-terminated fourth generation (G4) PAMAM dendrimer was transferred across the interface accompanied by the adsorption process. 16 The molecular encapsulation of 8-anilino-1-naphthalenesulfonate (ANS -) and its bimolecular derivative (bis-ANS 2-) in the carboxylate-terminated G3.5 PAMAM dendrimer was also investigated at the water|DCE interface as a function of pH and the Galvani potential difference. 17 A stable encapsulation of bis-ANS 2-compared with the monomeric ANS -was explained by the electrostatic two-point interaction of anionic sulfonate groups with protonated tertiary amines in the interior.…”
Section: Introductionmentioning
confidence: 99%
“…in the case of amphiphilic surfactant [9,[13][14][15][16] or transfer followed by adsorption e.g. in the case of polyelectrolyte, polypeptide or dendrimer transfer reactions [17][18][19][20][21][22][23][24]. Furthermore, one of the most biologically relevant systems is that of phospholipid monolayers in which adsorption and facilitated ion transfer reactions are closely related [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…S4, blue lines). These PMF responses were attributed to the ion transfer and adsorption of the dendrimer-bound fluorescent LC species at the organic side of the interface [1,8]. The slight enhancement of the fluorescence intensity confirmed the interaction between LC and the dendrimer as indicated from fluorescence spectra in aqueous solutions (Fig.…”
Section: S5mentioning
confidence: 63%
“…Fig. S1) [1]. In contrast to the electrochemical measurements, the potential dependences of the PMF responses associated with the adsorption of LC species at either side of the interface were .…”
Section: Fig S3mentioning
confidence: 65%